NT-proBNP (N-Terminal Pro-B-Type Natriuretic Peptide) and the Risk of Stroke Results From the BiomarCaRE Consortium - Di Castelnuovo A; Veronesi G; Costanzo S; Zeller T; Schnabel RB; de Curtis A; Salomaa V; Borchini R; Ferrario M; Giampaoli S; Kee F; Soderberg S; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Background and Purpose-NT-proBNP (N-terminal pro-B-type natriuretic peptide) is a risk factor for atrial fibrillation and a marker of cardiac function used in the detection of heart failure. Given the link between cardiac dysfunction and stroke, NT-proBNP is a candidate marker of stroke risk. Our aim was to evaluate the association of NT-proBNP with stroke and to determine the predictive value beyond a panel of established risk factors.Methods-Based on the Biomarkers for Cardiovascular Risk Assessment in Europe-Consortium, we analyzed data of 58 173 participants (50% men; mean age 52 y) free of stroke from 6 community-based cohorts. NT-proBNP measurements were performed in the central Biomarkers for Cardiovascular Risk Assessment in Europe laboratory. The outcomes considered were total stroke and subtypes of stroke (ischemic/hemorrhagic).Results-During a median follow-up time of 7.9 years, we observed 1550 stroke events (1176 ischemic). Increasing quarters of the NT-proBNP distribution were associated with increasing risk of stroke (P for trend < 0.0001; multivariable Cox regression analysis adjusted for risk factors and cardiac diseases). Individuals in the highest NT-proBNP quarter (NTproBNP > 82.2 pg/mL) had 2-fold (95% CI, 75%-151%) greater risk of stroke than individuals in the lowest quarter (NTproBNP < 20.4 pg/mL). The association remained unchanged when adjusted for interim coronary events during followup, and though it was somewhat heterogeneous across cohorts, it was highly homogenous according to cardiovascular risk profile or subtypes of stroke. The addition of NT-proBNP to a reference model increased the C-index discrimination measure by 0.006 (P=0.0005), yielded a categorical net reclassification improvement of 2.0% in events and 1.4% in nonevents and an integrated discrimination improvement of 0.007.Conclusions-In European individuals free of stroke, levels of NT-proBNP are positively associated with risk of ischemic and hemorrhagic stroke, independently from several other risk factors and conditions. The addition of NT-proBNP to variables of established risk scores improves prediction of stroke, with a medium effect size.